Enhancing Supply Chain Management for the Universities: ITESCM Model Perspective - Pathik, Bishwajit Banik; Habib, Dr. Md. Mamun (International Journal of Supply Chain Management, 2012)
This exploratory research addresses the application guidelines of ITESCM (Integrated Tertiary Educational Supply Chain Management) model for better Supply Chain Management in Universities. This study encompasses education supply chain, research supply chain and educational management as major constituents of ITESCM. Four main activities, includes education development, education assessment, research development, and research assessment in four aspects, namely Programs Establishment, University Culture, Faculty Capabilities, and Facilities were investigated at three decision levels. The ITESCM model was formulated based on the secondary data, i.e. analysis of the literature, and primary data, i.e. interviews with stakeholders of tertiary academic institutions. Model structures were defined and confirmed by 493 respondents, representing University administrators of world-ranking universities, faculty and staffs, employers, and graduates. The resulting structure was subsequently evaluated for accuracy and validity by multiple linear regression (MLR) analysis and the structural equation modeling (SEM) technique. This empirical study represents two contributions in terms of human resource contribution and research contribution to the end customer, i.e. the society. Model evaluation by actual implementation is suggested for prospective investors or current university administrators.